Trustworthiness of acquaintances in Peer-to-Peer overlay networks. (27th July 2009) - Watanabe, Kenichi; Enokido, Tomoya; Takizawa, Makoto
Various types of applications manipulate objects distributed in Peer-to-Peer overlay networks. An acquaintance peer of a peer p is a peer whose service the peer p knows and with which the peer p can directly communicate. We discuss types of acquaintance relations among peers and how much a peer trusts each acquaintance peer. We define the trustworthiness of each acquaintance peer in terms of the acquaintance relations. We discuss a Charge-Based Flooding (CBF) algorithm to find target peers so that more trustworthy areas in Peer-to-Peer overlay networks are more deeply searched. We evaluate the CBF algorithm compared with a TTL-based algorithm.